No final do arco-íris: estudo sobre a materialidade dos impressos produzidos para o curso de pedagogia da UNIVESP/UNESP - Oliveira, Karilene Margaret Delgado de [UNESP] (2013)
This work aims to identify aspects which characterize the writings currently addressed to teachers of the early years of basic education. Thus search unveil representations about the teachers, their professional culture and about the teacher training which are present in these reading materials and that, therefore, circulate in the educational field. The study is carried out by means of the examination of printed materials prepared for the course of pedagogy offered by Univesp/Unesp. It is a qualitative research, carried out by means of documentary study. The focus of the analyses was carried out about those printed materials refers to their materiality, to its morphological aspects that, that assumes, are revealing of the processes of production and circulation of these printed. The analysis of the data obtained in this study revealed that the printed material offered by UNIVESP/UNESP thins with the strong recovery that is currently given to the training of teachers, taken as privileged path to the transformation of school education. In this sense, the teacher education is regarded as permanent, to be held throughout the working life of teachers. The materiality of these printed suggests intentions towards the novelty, for possibilities of change and transformation of teachers. Processing for teachers and also change in form them, valuing the virtual resources. This material is also marked by the strong appreciation of the academic educational knowledge, designed opening for the novelty. Thus, the printed material presents itself as possibility to connect two worlds: that of teachers and the University. Through this closer contact, for which the printed material would act as a' bridge ', try to reinvent the teachers, through reflection on theirself and on their own teaching practices